An evaluation of instrumental enrichment with regard to its potential for improving children's adjustment to school - Chapman, Niels E (Cranfield University, 1987)
Instrumental Enrichment, an Intervention Program for Cognitive Modifiability, is a curricular package of methodology and materials designed to help teachers mediate in the learning experiences of pupils whose performance at school has been retarded by cultural deprivation. The originator of Instrumental Enrichment, Reuven Feuerstein, and the bulk of empirical research into his work, concentrates on the "thinking skills" aspect of how children process their perceptions of reality and takes little account of how they feel about those perceptions. Nonetheless, Feuerstein's theory seems to me to contain a blueprint for a more balanced approach to the curriculum, and in this thesis I seek to evaluate its potential for promoting affective and conative aspects of children's development as well as the cognitive aspect. My evaluation is limited to a study of the effects of Instrumental Enrichment on children's adjustment to school; although increased psychological integration, which I find in many cases where pupils rate their adjustment as having improved, is hopefully manifest both inside and outside the classroom. Indeed, I go so far as to say that implementation of Feuerstein's methodology constitutes a political force in favour of the sovereignty of the individual learner and democratic procedures in education. My first chapter is an attempt to furnish the reader with the theoretical background and terminology associated with Instrumental Enrichment. It is followed by a chapter which describes from a practitioner's perspective how Feuerstein's theory, especially his concept of the teacher as a mediator between children and their culture, translates into classroom tasks. The third chapter provides operational definitions of how the effects of Instrumental Enrichment were measured in the course of a two-year experiment on primary and secondary pupils in Buckinghamshire; it defines my use of the Child at School - a new behaviour schedule, the Repertory Grid Technique, and ability and attainment tests. In the fourth chapter, I record and comment on the mean ratings and scores obtained by Buckinghamshire pupils; results are subjected to analysis of covariance. Finally, I infer some support for the hypothesis that Instrumental Enrichment can improve children's adjustment to school, and note the implications of this finding for policies on curriculum planning and teacher training.